Case Report: Malacoplakia Due to E. coli With Cryptococcus albidus Infection of a Transplanted Kidney in a Patient With Recurrent Urinary Tract Infection - Yan, Ziyan; Deng, Wenfeng; Wang, Yuchen; Liu, Yanna; Sun, Hengbiao; Xia, Renfei; Zeng, Wenli; Geng, Jian; Chen, Gui; He, Xiaolong; Xu, Jian; Wu, Chin-Lee; et al. (Frontiers in Medicine, 2021)
Background: Colonization of Cryptococcus rarely occurs in a graft. This study reports a case of cryptococcoma caused by Cryptococcus albidus in a transplanted kidney, with detailed pathology and metagenome sequencing analysis. Case Presentation: We presented a case of cryptococcoma in the genitourinary system including the transplant kidney, bladder, prostate, and seminal vesicles caused by Cryptococcus albidus in a renal-transplant recipient. Metagenome sequencing was conducted on a series of samples obtained from the patient at three different time points, which we termed Phase I (at the diagnosis of cryptococcoma), Phase II (during perioperative period of graftectomy, 3 months after the diagnosis), and Phase III (2 months after graftectomy). Sequencing study in the Phase I detected two and four sequences of C. albidus respectively in cerebrospinal fluid (CSF) and feces, with resistant Escherichia coli 09-02E presented in urine and renal mass. A three-month antibiotic treatment yielded a smaller bladder lesion but an enlarged allograft lesion, leading to a nephrectomy. In the Phase II, two sequences of C. albidus were detected in CSF, while the E. coli 09-02E continued as before. In the Phase III, the lesions were generally reduced, with one C. albidus sequence in feces only. Conclusions: The existence and clearance of Cryptococcus sequences in CSF without central nervous system symptoms may be related to the distribution of infection foci in vivo, the microbial load, and the body’s immunity. Overall, this study highlights the need for enhanced vigilance against uncommon types of Cryptococcus infections in immunocompromised populations and increased concern about the potential correlation between E. coli and Cryptococcus infections.